Promotion of colorectal cancer cell death by ezetimibe via mTOR signaling-dependent mitochondrial dysfunction - Zheng, Yuanyuan; Yang, Wenjuan; Jia, Yewei; Ji, Jie; Wu, Liwei; Feng, Jiao; Li, Yan; Cheng, Ziqi; Zhang, Jie; Li, Jingjing; Dai, Weiqi; Xu, Xuanfu; et al. (Frontiers in Pharmacology, 2023)
Introduction: Colorectal cancer (CRC) is the fourth most common cancer worldwide, with high morbidity and mortality rates. In recent years, high-fat diet has been shown to increase CRC morbidity, highlighting the possibility of the application of hypolipidemic drugs for CRC treatment. In this study, we preliminarily evaluated the effects and mechnisms of ezetimibe against CRC through the blockage of lipid absorption in small intesine. Methods: In this study, CRC cell proliferation, invasion, apoptosis, and autophagy were evaluated using cellular and molecular assays. Fluorescent microscopy, and a flow cytometric assay were used to assess mitochondrial activity in vitro. A subcutaneous xenograft mouse model was used to evaluate the effects of ezetimibe in vivo. Results: We found that ezetimibe inhibited CRC cell proliferation, and migration, and facilitated autophage-associated apoptosis in HCT116 and Caco2 cells. Ezetimibe-induced mitochondrial dysfunction in CRC cells was found to be correlated with mTOR signaling activity. Discussion: Ezetimibe exhibits effects against CRC through the promotion of cancer cell death via mTOR signaling-dependent mitochondrial dysfunction, highlighting its potential value in CRC therapy.